Legal Perspectives on the Idea of Agonistic Planning - Durner, Wolfgang (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
Historically, the emergence of planning law and the juridification of planning in Germany did not follow any planning theory, but a logic inherent to the constitutional state. Only in small number of cases did the legislature or the judiciary adopt elements of planning theories, most of which were developed much later. Law defines itself by its strict claim to be obeyed. Therefore, the requirements of planning law may conflict with the recommendations of normative planning theories and then claim precedence over these. Nevertheless, with regard to the viability of some proposals of agonistic planning theories, legal borderlines arise. This paper deals with these borderlines. However, the goal of agonistic theories of planning coincides with the basic function of planning law to pacify conflicting interests and to reach acceptable solutions. Opponents of state planning projects thus are entitled to participate in planning procedures and to file far-reaching lawsuits. However, the legal order also sets limits to legitimate resistance to democratic planning and cannot refrain from distinguishing between legitimate and illegitimate forms of rejection.
Keywords: Spatial planning; Planning law; History of planning law; Planning theory; Agonistic planning